THE INFLUENCE OF MATHEMATIC CREATIVE ABILITIES ON STUDENT LEARNING OUTCOMES - Ninawati, Mimin; Suryadi, Didi; Herman, Tatang (International Conference on Elementary Education, 2018)
The purpose of this study was to see the effect of mathematical creative thinking skills on student learning outcomes. The research method used is quantitative research. The sample used in this study were fourth grade elementary school students who were selected by purposive sampling technique. While the design used in this study is to use the pretest and posttest One Group Design. The data in this study were obtained from the prestest and postest values which were analyzed statistically by the Paired Sample T-Test. The result of the research means that there is a significant influence between the influence of mathematical creative thinking skills on learning outcomes of elementary school students